AGILE 2015 Geographic Information Science as an Enabler of Smarter Cities and Communities - Bacao, Fernando; Santos, Maribel Yasmina; Painho, Marco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This is a book is a collection of articles that will be submitted as full papers to the AGILE annual international conference. These papers go through a rigorous review process and report original and unpublished fundamental scientific research. Those published cover significant research in the domain of geographic information science systems. This year the focus is on geographic information science as an enabler of smarter cities and communities, thus we expect contributions that help visualize the role and contribution of GI science in their development.
Exploring the potential of combining taxi GPS and Flickr data for discovering functional regions -- A Semantic Region Growing Algorithm: Extraction of Urban Settings -- Central Places in Wikipedia -- Applications of Volunteered Geographic Information in Surveying Engineering: A first approach -- A Gamification Framework for Volunteered Geographic Information -- Privacy Preserving Centralized Counting of Moving Objects -- Enabling Semantic Search and Knowledge Discovery for ArcGIS Online: A Linked-Data-driven Approach -- Real-time anomaly detection from environmental data streams -- Towards Real-Time Processing of Massive Spatio-Temporally Distributed Sensor Data: A Sequential Strategy Based on Kriging -- Statistical learning approach for wind speed distribution mapping: UK as a case study.
Keywords: Geography; Geographical information systems; Geography; Geographical Information Systems/Cartography.; Electronic books